PENGARUH KEMANFAATAN, KEMUDAHAN PENGGUNAAN, KEPERCAYAAN KONSUMEN DAN DAYA TARIK PROMOSI TERHADAP MINAT BELI DI GRAMEDIA ONLINE - Siburian, Cahaya Ermauli; Riki (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2024)
This research aims to determine the influence of usefulness, ease of use, consumer trust and promotional attractiveness on purchasing interest at Gramedia Online. This research uses a census method, namely recording the entire existing population. And the sample in this study was 100 Gramedia Batam customers who had visited the Gramedia Online website. Data was collected using a questionnaire technique. In the results of this research, it was obtained that the variable equation of usefulness, consumer trust and promotional attractiveness had a significant effect on buying interest, while the ease of use variable had no significant effect on buying interest. Meanwhile, the R square value is 0.872 or 87.3%, meaning the independent variable is able to explain the dependent variable by 87.3%. Meanwhile, the remaining 12.7% is influenced by other variables not included in this research.